Clinical and radiological results on the fixation of Neer type 2 distal clavicle fractures with a hook plate - Erhan Şükür; Yusuf Öztürkmen; Yunus Emre Akman; Mustafa Güngör (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to analyze the clinical and functional results of hook plate fixation in Neer type 2 distal clavicle fractures. Methods: We retrospectively analyzed 16 patients (11 males, 5 females) who were diagnosed with Neer type 2 distal clavicle fractures and treated with hook plate fixation between 2013 and 2014. Mean age was 38 (range: 27–61), and mean follow-up time was 14.3 (range: 12–18) months. Complications seen on radiographs were implant failure and subacromial osteolysis. The clinical results were evaluated with modified UCLA (University of California Los Angeles) scoring system. Results: Bone union was achieved in all patients at the end of the first 4 months. Mean modified UCLA score was 32.75 (range 31–35). In 12 patients (68%), the implants had to be removed due to complications. After removal, the complaints regressed and shoulders' range of motion increased. Conclusion: Clinical and radiological results on the fixation of Neer type 2 distal clavicle fractures with a hook plate are good in terms of fracture union and function. The major disadvantage of the method was the requirement of early implant removal due to the hardware related complications and good results can be achieved only after plate removal. Optimizing the length of hook plate may lower the rate of complications. Level of evidence: Level IV, Therapeutic study. Keywords: Distal clavicle fracture, Neer type 2, Fixation, Hook plate